FEATURES OF RESULT-ORIENTED BUDGETING IN THE CONTEXT OF UZBEKISTAN - Primova N.I., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article examines the features of results-oriented budgeting, which is one of the current directions of reforming the budget process in the Republic of Uzbekistan. The study analyzes the theoretical foundations of ROB, international experience, the socio-economic significance of its implementation in the conditions of Uzbekistan, as well as emerging problems and ways to solve them. It has been established that the specifics of implementing the ROB system in Uzbekistan are related to factors such as medium-term planning, administrative reforms, reference infrastructure, and personnel training. As a result of the research, practical proposals were developed for the phased transition to ROB, improvement of the regulatory framework, improvement of personnel qualifications, and implementation of a medium-term planning system.